The Maintenance of River Catfish (Mystus nemurus CV) in Recirculation System and Biofloc Combination With Diferently Density of Basil Plant (Ocimum sanctum L.) - Yudistira '; Mulyadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from 20 August to 20 September of 2014 at the Breeding Unit Laboratory, Faculty of Fisheries and Marine Sciences University of Riau, Pekanbaru. This study aims to determine the growth and survival rate of River Catfish (Mystus nemurus CV) reared in resisculation system and biofloc combination with diferently density of basil plant (Ocimum santum L.) using the experimental method Completelly Randomized Design (CRD) with one factor, three treatments and three replication which had different level comparison of basil plant density, there are: P1 (density of 30 stems of basil plants), P2 (density of 45 stems of basil plants) and P3 (density of 60 stems of basil plants). The results showed that the best treatment is P3 treatment with the absolute weight growth of 8.3 g, absolute length growth 9 cm, daily weight growth rate of 5.03% and the survival rate of 95%. Water quality parameters during recorded research period are ammonia (NH3) from 0.30 to 0.50 mg/L, nitrite (NO2) from 0.06 to 0.25 mg/L, nitrate (NO3) ranged from 0.13 to 1.20 mg/L, temperature 27-30oC, 5-6 OF pH, dysolved ovygen (DO) of 3.0 to 3.4 mg/L and CO2 of 6.89-10.58 mg/L.Keywords: River catfish (Mystus nemurus CV) Biofloc, Recirculation